INDUKSI PERKECAMBAHAN PADA BIJI KARET (Hevea brasiliensis Muell) DENGAN SISTEM PERENDAMAN DAN TANPA PERENDAMAN AIR - Kamsia Dorliana Sitanggang; Khairul Rizal (UNIVERSITAS LABUHANBATU, 2020)
This study aims to see the differences in the speed of sprout growth with immersion systems and without water immersion. The results showed that there were differences percentage of seeds germinated between seeds that were given water immersion for 12 hours (85%) and were not given water immersion (65%). For the other parameter average days of sprouting, where the seeds that are given water immersion are more quickly induced by sprouts as much as 60% age 7 days after seedling, compared not given water immersion can only be induced by 40%. Likewise, the 17th day after the seedlings were induced by 85% for soaking seeds and 65% for seeds that were not soaking. Keywords: Rubber, Sprout, Water immersion